Principles of Prevention of Dental Diseases in Children in Modern Conditions (Eurasian Research Bulletin, 2023)
The occurrence of dental caries in children is inextricably linked with the negative impact of cariogenic factors: unbalanced diet, high carbohydrate content in food, poor oral hygiene, environmental violations and preventive measures.